Introduction to engineering plasticity : fundamentals with applications in metal forming, limit analysis and energy absorption /: fundamentals with applications in metal forming, limit analysis and energy absorption. (2022) - Yu, T. X (Tongxi), 1941-; Xue, Pu
No abstract available